2D Sn-doped ZnO ultrathin nanosheet networks for enhanced acetone gas sensing application. Issue 2 (1st February 2017) - Al-Hadeethi, Yas; Umar, Ahmad; Al-Heniti, Saleh. H.; Kumar, Rajesh; Kim, S.H.; Zhang, Xixiang; Raffah, Bahaaudin M.
Abstract: In this paper, we report the synthesis, characterizations and gas sensing application of 2D Sn-doped ZnO ultrathin nanosheet networks synthesized by a simple and facile hydrothermal process. The synthesized nanosheets were characterized using several techniques in terms of their morphological, structural, optical and compositional properties. The detailed characterizations confirmed that the nanosheets are pure, grown in high-density, possessing well-crystalline wurtzite hexagonal phase and exhibiting good optical properties. Further, the synthesized nanosheets were used as functional material to develop nanosensor device by coating it on the alumina substrate with suitable electrodes. The fabricated sensor device was tested towards acetone gas which exhibited a maximum sensitivity of 5.556 (Ra/Rg) for 200 ppm of acetone at 320 °C.